Os desafios da aprendizagem matemática no ensino médio : um reflexo da aprendizagem matemática do ensino fundamental - Leseux, Sandro Luiz (2017)
In light of the multiple points of view and perspectives from which are available to analyze current public policies for basic education, as well as weaknesses in the teaching and learning process of mathematics, this research, using a qualitative approach, sought to discuss public education from this perspective: ―what is the scenario of the mathematics learning, at the end of middle school, for the continuity of mathematics learning in high school?‖ The main objective of this study was to investigate the presence or absence of appropriate mathematical skills in high school freshman students and the continuity of learning mathematical concepts during the final stage of high school education. Considering the importance and at the same time the complexity of choosing the categories of analysis, since it requires an intense back and forth to the analyzed material and underlying theories, I chose to investigate based on three categories of analysis: Public Education Policies; Mathematics Learning in Middle School; Continuity of Mathematics Learning in High School, in order to enable an understanding of the object of study. For the study of the Public Education Policies I used the official documents: ―Law of Directive and Basis (LDB)‖, ―National Curricular Guidelines for Middle Education (DCNEB)‖ and ―Curricular Guidelines for Middle Education of the State of Mato Grosso (OCEB)‖, having as the scope, the objectives and purposes of middle school education, high school education, as well as the learning objectives established for mathematics as a curricular component. Regarding mathematics learning and the continuity of mathematics learning in high school this research was anchored both in the official documents mentioned above and on theoretical basis that address such topics. In this way and with the purpose of answering the problem of this research, it was defined as context, an Urban State School located in the municipality of Comodoro-MT. As subjects of the research, were invited two mathematics teachers who work in the first year of high school and 85 students of this same year / grade within the same school researched. As instruments for the data output, a mixed questionnaire, semi-structured interview, evaluative test of mathematics and documentary analysis were used. From the theoretical contribution and the interpretation and data analysis it was possible to observe that the students entering high school present significant difficulties in mathematics and that these are an issue of the middle school. It seems that during the years of the elementary and middle school, a considerable number of students have not been able to appropriate even the mathematical concepts considered basic and fundamental for the continuity of learning of mathematics during this same stage nor during high school. Therefore, the data produced through this research may reveal that the non-learning of mathematics in high school is not only caused by issues of elementary and middle school education, but also a reflection of the non-learning of the mathematics, which is established along the early years and thus the continuity of mathematics learning in later school years is significantly weakened and presents multiple challenges that need to be overcome.